Pembatasan Kepala Daerah Baru dalam Mengganti Sekretaris Daerah: Tinjauan Yuridis - Muhamad Chabib F. (Jurnal Hukum Lex Generalis, 2025)
The Regional Secretary (Sekda) has a strategic role in the implementation of local government as the highest leader of the civil service and the driving force of the bureaucracy. However, in practice, the replacement of the Sekda by a new head of region often causes controversy, especially if it occurs within the first six months of the term. Based on Law Number 10 of 2016, newly appointed regional heads are prohibited from replacing officials, including the Regional Secretary, within six months of their appointment, except with written approval from the Minister of Home Affairs. This study aims to examine this restriction from a legal perspective and its implications for the principle of the rule of law. The research method used is normative juridical, with an approach based on regulations and the principles of state administrative law. The results of the study indicate that the limitation aims to prevent the abuse of power, maintain bureaucratic neutrality, and ensure the continuity of a professional and accountable government. However, in Article 162 paragraph (3) of the Regional Election Law, there is a lack of legal certainty; the regulation should end at the time of the election organizers, so the actions of the newly appointed regional heads are no longer under the legal authority of the Regional Election Law.